Exploiting MMR Pathways in Plasmodium as Novel Antimalarial Targets: Opportunities and Challenges - Tarique, Mohammed; Sain, Ziaullah; Ahmad, Yusuf (International Journal of Pharmaceutical Investigation, 2026)
Malaria, which is caused by Plasmodium parasites, remains a major international health issue, especially in developing countries. The problem of drug resistance has become a major concern, especially with respect to artemisinin-based combination therapies (ACTs). Another approach that has been suggested but not well explored is the targeting of parasite-specific DNA repair mechanisms, such as the DNA mismatch repair (MMR) pathway. MMR is crucial for genome stability by correcting replication errors, and any defect in MMR has a significant impact on parasite survival, adaptation, and drug resistance. Recent studies have shown that Plasmodium has a distinct, possibly divergent MMR system compared to the human host, which could be exploited for therapeutic purposes. Disrupting MMR pathways may make parasites more sensitive to DNA damage, reduce their ability to develop resistance, and increase the effectiveness of current antimalarial drugs. However, there are some challenges, including a poor understanding of Plasmodium MMR components, possible functional redundancy with other repair systems, and the potential for off-target effects. In this review, we summarize present knowledge of MMR pathways in Plasmodium, discuss their potential as new antimalarial targets, and outline hypothetical models for MMR-based therapeutic approaches. We also discuss the major opportunities and challenges that must be overcome to turn this concept into actual antimalarial interventions. Targeting MMR pathways may provide new ways of combating malaria and help in the fight against the increasing resistance to drugs
Keywords: Biomarkers. Drug Resistance; DNA damage; DNA Repair; Malaria; Mutation; MMR; Parasites.